Problem solving method an approach to revitalize the teaching of social studies to academically superior children in the intermediate grades - Epistola, Nicetas V. 1933- (1967)
The objective of the study is to explore the possibility of revitalizing the teaching of social studies to the academically superior children in the intermediate level. It looked into the present status of social studies in the elementary school curriculum, the social studies for the academically superior children, and the problem-solving approach in the teaching-learning process, and the problem-solving method: a suggested approach to revitalize the teaching of social studies to the academically superior.